Choriocarcinoma - Varied Presentations (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Choriocarcinoma is a highly malignant tumour that originates in developing trophoblast of pregnancy. It is a potentially fatal disease but current management protocol has turned the prognosis highly favourable.Gestational choriocarcinoma is not a rare disease in our country. Various mode of presentation sometimes makes it  difficult to diagnose.Eleven cases of choriocarcinoma were presented here along with treatment modalities and prognosis. Two patients expired during treatment while other respond well with chemotherapy. Early diagnosis and appropriate treatment have better prognosis. DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12464 J Bangladesh Coll Phys Surg 2012; 30: 145-150